Primary Headache among University Students: Across Sectional Study - Mohamed M. Abd El-Mawgod, Hashem H A, Yahia Abdelgawad Elsayed Elboraei (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Recent studies have shown an increase in prevalence of different types of headache among students all over the world. Objective: To determine the prevalence of, triggering and associated factors primary headaches among medical students with the aim of increasing awareness about this particular health issue. Participants and Methods: Descriptive cross-sectional study was conducted from September to December 2019 on 196 students, college of medicine, Northern Border University (NBU). Results: A one hundred and nighty six student participants, their mean age was 21.73 ±15.6 with prevalence of headache 88.7% among them. headache participants aged 22 years and younger accounting for 88.7% compared to 88.9% for those aged more than 22 years with statistically insignificant finding. The study revealed that, 100% of the female participants reported headache compared to 80% of males with statistically significant results (p<0.001), OR 0.8 (0.72-0.87). Higher grade group (more than 3rd year) reported headache 92.4% compared to 85.6% for lower grade group (3rd and less) but the difference was statistically none significant. Regarding effect of BMI on headache prevalence among our Participants showed, those with normal weight were insignificantly more likely to suffer from headache 90.6% compared to overweight and obese 85.5% p>0.05. Most common cited triggering factors were sleep disturbance (86.2%), noise exposure (83.3%), over study (81.6%) and fatigue (75.9%), More than two thirds (69%) mentioned anxiety. More than half (60.9%) reported bright light and hunger sensation (59.8%). more than two thirds (72.4%) of the participants had social troubles in the last year. Most of the participants (60.9%) received analgesics for headache and physician was the source of advice in 33% Conclusion: Primary headache is highly prevalent among medical students with female predominant which was mainly related to sleep disturbance, noise exposure, over study, fatigue, hunger sensation. social troubles reported in more than two thirds of headache participants and Most of the participants (60.9%) received analgesics for headache and physician was the source of advice in 33% only.